2020
DOI: 10.5781/jwj.2020.38.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Review on Mitigation of Welding-Induced Distortion Based on FEM Analysis

Abstract: Welding distortion is an unavoidable issue due to localized expansion and contraction during the heating and cooling cycles, and has a negative effect on the fabrication process. However, mitigating weld distortion to meet product requirements is a challenging task, because welding shrinkage can't be prevented, only controlled. This paper provides a comprehensive literature review of various techniques to reduce and optimize the deformation induced by welding in the design stage and manufacturing process. Fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Wu suggested that mechanical and thermal balance techniques be developed during the welding process to control welding distortion by reducing welding thermal gradients and producing a tensile stress field near the welded region. A review of these approaches would be beneficial in order to fully understand the main mechanism of mitigating welding-induced distortion and to select the most appropriate method for minimizing deformation based on realistic fabrication demands [ 22 ]. However, welding distortion can be precisely predicted during the manufacturing process while accounting for both local shrinkage and root gap.…”
Section: Introductionmentioning
confidence: 99%
“…Wu suggested that mechanical and thermal balance techniques be developed during the welding process to control welding distortion by reducing welding thermal gradients and producing a tensile stress field near the welded region. A review of these approaches would be beneficial in order to fully understand the main mechanism of mitigating welding-induced distortion and to select the most appropriate method for minimizing deformation based on realistic fabrication demands [ 22 ]. However, welding distortion can be precisely predicted during the manufacturing process while accounting for both local shrinkage and root gap.…”
Section: Introductionmentioning
confidence: 99%
“…Such a model needs less analysis time and is consistent with the experimental results to some extent. Recently, Wu and Kim [22] provided a comprehensive literature review of various techniques to reduce and optimize the deformation induced by welding in the design stage and manufacturing process. Rong et al [23] provided the research status on the welding distortion and residual stress prediction by FE analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize trial and error, it is advantageous to verify design feasibility through the finite element method at the design stage, and this is an approach widely used in academia as well as in industry. The finite element method has the advantage of being able to verify design feasibility at a much lower cost compared with experiments or deriving the optimal design through case studies under various conditions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%